(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines theoretical and methodological issues related to the development and distribution of productive forces in the Kyrgyz Republic. Based on an analysis of the distribution of productive forces across the country over the past ten years, it concludes that the country is uneven, imperfect, and lacks a systematic and scientific approach. This leads to undesirable consequences, including varying standards of living across regions, internal and external migration, and excessive concentration of industry and population in a single agglomeration. Based on international experience and current trends in production organization—clustering, specialization, the creation of special zones, etc.—recommendations are provided for defining criteria for the future distribution of productive forces.